TC2N: A Novel Vital Oncogene or Tumor Suppressor Gene In Cancers - Li, Hanyang; Fang, He; Chang, Li; Qiu, Shuang; Ren, Xiaojun; Cao, Lidong; Bian, Jinda; Wang, Zhenxiao; Guo, Yi; Lv, Jiayin; Sun, Zhihui; Wang, Tiejun; et al. (Frontiers in Immunology, 2021)
Several C2 domain-containing proteins play key roles in tumorigenesis, signal transduction, and mediating protein–protein interactions. Tandem C2 domains nuclear protein (TC2N) is a tandem C2 domain-containing protein that is differentially expressed in several types of cancers and is closely associated with tumorigenesis and tumor progression. Notably, TC2N has been identified as an oncogene in lung and gastric cancer but as a tumor suppressor gene in breast cancer. Recently, a large number of tumor-associated antigens (TAAs), such as heat shock proteins, alpha-fetoprotein, and carcinoembryonic antigen, have been identified in a variety of malignant tumors. Differences in the expression levels of TAAs between cancer cells and normal cells have led to these antigens being investigated as diagnostic and prognostic biomarkers and as novel targets in cancer treatment. In this review, we summarize the clinical characteristics of TC2N-positive cancers and potential mechanisms of action of TC2N in the occurrence and development of specific cancers. This article provides an exploration of TC2N as a potential target for the diagnosis and treatment of different types of cancers.